Antiphospholipid Antibodies and Antiphospholipid Syndrome during Pregnancy: Diagnostic Concepts - Levy, Roger A.; dos Santos, Flavia Cunha; de Jesús, Guilherme R.; de Jesús, Nilson R. (Frontiers in Immunology, 2015)
Antiphospholipid syndrome comprises of a wide spectrum of clinical and obstetric manifestations linked to the presence of antiphospholipid antibodies. APS was described in the context of lupus and later as an isolated syndrome or primary APS. The Classification Criteria was designed for the definition of APS in epidemiologic and clinical studies is generally misused for clinical diagnostic decisions on an individual basis. The presence of aPL, especially the lupus anticoagulant test, is known to be a recurrence predictor for arterial events and fetal death. When the serologic assays are used it is important that the validated tests for anticardiolipin and anti-beta 2 glycoprotein I and cut-off are employed. Pathogenic mechanisms are various, beyond the inhibition of anticoagulant action of beta 2 glycoprotein I and other natural anticoagulants, including cell-mediated events involving endothelial and dendritic cells, monocytes and platelets. The mechanisms are not self-exclusive and may in fact be related, offering different targets for potential future therapies. During pregnancy a high-risk care setting, following a protocol of tests and prediction of events, is imperative. The relationship of aPL and infertility is not clear, w